ANALISIS NILAI EKONOMI KAWASAN HUTAN MANGROVE DENGAN PENDEKATAN WILLINGNES TO PAY DESA TANJUNG SUNGKAI KECAMATAN PULAULAUT TANJUNG SELAYAR KABUPATEN KOTABARU - Kardilla Kardilla; Sari Mayawati; Muhammad Naparin (Jurnal Sylva Scienteae, 2026)
This study aims to analyze the economic value of the mangrove forest area in Tanjung Sungkai Village, Pulaulaut Tanjung Selayar District, Kotabaru Regency, using the Willingness to Pay (WTP) method. In this study, data were collected from 30 respondents who are residents around the mangrove forest. The analysis results show that the total community WTP for mangrove forest conservation reached IDR 1,845,000, with an average WTP per respondent of IDR 61,500. Although there is a willingness to pay, the proportion of respondents who are willing to pay a higher amount tends to be low, reflecting a lack of understanding of the economic and ecological value of mangrove forests. This study also found that there is no significant linear correlation between the economic value of mangrove forests and community income, with a Pearson correlation coefficient of 0.000560512.  This shows that other factors, such as education and environmental awareness, play an important role in determining the value perceived by the community towards mangrove forests. From the results of this study, it is hoped that it can contribute to the development of mangrove forest conservation policies and programs, as well as increase public awareness of the importance of mangrove forests for their social and economic lives.